2014
DOI: 10.1094/pdis-05-13-0482-re
|View full text |Cite
|
Sign up to set email alerts
|

PythiumSpecies and Isolate Diversity Influence Inhibition by the Biological Control AgentStreptomyces lydicus

Abstract: Weiland, J. E. 2014. Pythium species and isolate diversity influence inhibition by the biological control agent Streptomyces lydicus. Plant Dis. 98:653-659.Disease control of soilborne pathogens by biological control agents (BCAs) is often inconsistent under field conditions. This inconsistency may be partly influenced by pathogen diversity if there is a differential response among pathogen species and isolates to selected BCAs. The responses of 148 Pythium isolates obtained from soil at three forest nurseries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…was also determined in an in vitro assay that evaluated growth inhibition of several Pythium spp. isolates from Oregon nurseries (Weiland, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…was also determined in an in vitro assay that evaluated growth inhibition of several Pythium spp. isolates from Oregon nurseries (Weiland, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…on geranium than snapdragon. It has been shown that the efficacy of biological control agents in controlling soilborne diseases can be variable (Handelsman and Stabb, 1996;Leisso et al, 2009;Linderman et al, 2008;Weiland, 2014;Whipps and McQuilken, 2009). Inconsistent results may be related to biotic and abiotic factors that affect the antagonistic properties of the biocontrol agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative explanation for the failure of biocontrol to work in our study may be that the biocontrol agents were not equally active against all members of the soilborne pathogen community at each nursery. For example, we know that the Pythium community at each nursery is unique (Weiland, 2011) and that the biocontrol agent S. lydicus WYEC108 does not inhibit all Pythium species and isolates from forest nurseries to the same degree (Weiland, 2014). Pythium species such as P. ultimum were inhibited less by S. lydicus than other species like P. irregulare (Weiland, 2014).…”
Section: Weiland Page 17 Crop Protectionmentioning
confidence: 99%
“…For example, we know that the Pythium community at each nursery is unique (Weiland, 2011) and that the biocontrol agent S. lydicus WYEC108 does not inhibit all Pythium species and isolates from forest nurseries to the same degree (Weiland, 2014). Pythium species such as P. ultimum were inhibited less by S. lydicus than other species like P. irregulare (Weiland, 2014). Therefore, disease control may be compromised in soils where both pathogens are present.…”
Section: Weiland Page 17 Crop Protectionmentioning
confidence: 99%